Oxygen-rich interface enables reversible stibium stripping/plating chemistry in aqueous alkaline batteries - Zhang, Haozhe; Liu, Qiyu; Zheng, Dezhou; Yang, Fan; Liu, Xiaoqing; Lu, Xihong (Nature communications, 2021)
Aqueous alkaline batteries see bright future in renewable energy storage and utilization, but their practical application is greatly challenged by the unsatisfactory performance of anode materials. Herein, we demonstrate a latent Sb stripping/plating chemistry by constructing an oxygen-rich interface on carbon substrate, thus providing a decent anode candidate. The functional interface effectively lowers the nucleation overpotential of Sb and strengthens the absorption capability of the charge carriers (SbO 2 − ions). These two advantageous properties inhibit the occurrence of side reactions and thus enable highly reversible Sb stripping/plating. Consequently, the Sb anode delivers theoretical-value-close specific capacity (627.1 mA h g −1 ), high depth of discharge (95.0%) and maintains 92.4% coulombic efficiency over 1000 cycles. A robust aqueous NiCo 2 O 4 //Sb device with high energy density and prominent durability is also demonstrated. This work provides a train of thoughts for the development of aqueous alkaline batteries based on Sb chemistry. The practical application of aqueous alkaline battery is confined by limited choice of anode. Here, the authors demonstrate an oxygen-rich interface induced reversible Sb stripping/plating chemistry that provides a promising Sb metal anode with fast reaction kinetics and favourable stability.